2019
DOI: 10.3390/ijms20174250
|View full text |Cite
|
Sign up to set email alerts
|

mRNA and miRNA Expression Analysis Reveal the Regulation for Flower Spot Patterning in Phalaenopsis ‘Panda’

Abstract: Phalaenopsis cultivar ‘Panda’ is a beautiful and valuable ornamental for its big flower and unique big spots on the petals and sepals. Although anthocyanins are known as the main pigments responsible for flower colors in Phalaenopsis, and the anthocyanins biosynthetic pathway in Phalaenopsis is generally well known, the detailed knowledge of anthocynins regulation within the spot and non-spot parts in ‘Panda’ flower is limited. In this study, transcriptome and small RNA libraries analysis from spot and non-spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 47 publications
3
18
0
Order By: Relevance
“…5). As studies have shown the positive correlation of anthocyanin accumulation with CHI [11,72], the downregulation of CHI encoding gene in colored petals could be due to the feedback regulation [30]. Similarly, we observed strong downregulation of two F3H(CYP75B1) encoding genes in the albino labellum and petals (Fig.…”
Section: Critical Pathways Involved In Regulation Of Flower Color Variationsupporting
confidence: 76%
See 1 more Smart Citation
“…5). As studies have shown the positive correlation of anthocyanin accumulation with CHI [11,72], the downregulation of CHI encoding gene in colored petals could be due to the feedback regulation [30]. Similarly, we observed strong downregulation of two F3H(CYP75B1) encoding genes in the albino labellum and petals (Fig.…”
Section: Critical Pathways Involved In Regulation Of Flower Color Variationsupporting
confidence: 76%
“…5). Studies have shown that differential expression of genes encoding these key enzymes (CHS, CHI, F3H, FLS and DFR) play critical role in anthocyanin accumulation and affect the flower color phenotype [13,21,27,72]. Importantly, we observed strong downregulation of CHS encoding gene in albino labellum.…”
Section: Critical Pathways Involved In Regulation Of Flower Color Variationmentioning
confidence: 51%
“…This result revealed that OAGL6-2 formed an L′ complex with OAP3-1 in the lateral sepals; in turn, this complex controls the activation of PeMYB11 (Fig. 2j), which has been thought to be associated with red spot formation 22,27 . Silencing OAGL6-2 caused a severe reduction in L ′ complex function, subsequently downregulating PeMYB11 expression ( Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Flower spot patterning could affect the ornamental value of some orchids and may play a significant role in the interaction with pollinators. Zhao et al used a transcriptome analysis in the anthocyanin biosynthetic pathways of Phalaenopsis "Panda" to identify differentially expressed genes (DEGs) [2]. They further confirmed that some candidate structure genes among the DEGs expressed in significantly higher levels in spot tissues using qPCR analysis.…”
Section: Pigment Formationmentioning
confidence: 95%